Peran Regulasi Emosi Terhadap Kenakalan Remaja di Dasan Erot Kelurahan Kembang Sari - Khotmi, Nurmaulia; Dita Pebriana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The adolescent phase is one of the phases in human development that is very unique. During adolescence, individuals experience many changes including physiological and psychological changes. Physiologically and psychologically there are differences between the emotional management of male and female adolescents. With these differences, there will be differences in the way of thinking, feeling and behaving. Likewise, the juvenile delinquent behavior that occurs in dasan Erot is due to the lack of self-control ability so that it is easily influenced if there is a trigger for delinquency. The purpose of this study was to determine whether there is a role of self-control on the tendency of delinquent behavior in adolescents in dasan erot, kembang sari village. The subjects of this study were adolescents in Dasan Erot. The method in this research is a qualitative method of Phenomenology type. Phenomenology is one type of qualitative research, where researchers collect data by interviewing and observing participants to find out the essential phenomena of participants in their life experiences. The results of this study indicate that the role of emotional regulation in adolescents is very important to be able to control themselves so that they are not easily provoked and affected by situations that can cause commotion between adolescents.